Plánování vyučovací hodiny - Vodehnal, Jiří (Univerzita Pardubice, 2008)
The thesis deals with planning – projecting the lesson as one of the areas of teacher’s professional competence, is sectioned into two parts – theoretical and practical. In the theoretical part difficulties in planning the teaching unit are analysed in all aspects. The theory is further confronted with results of the research focused on the planning of English language teaching.
Lesson planning
Keywords: vyučovací hodiny; plány hodin; přípravné procesy; učitelé začátečníci; zkušení učitelé; žáci; lessons; lesson plans; preparatory processes; novice teachers; experienced teachers; pupils